Features and prospects of ethnocultural identity of the Kazakh diaspora in China - Erzhan Bulanov, Nazgul Baigabatova, Saira Rakhipova, Amangeldy Tolamissov,; Myrzatayeva, Zabira (Opción)
This article is devoted to the research of the specifics of the formation of the ethnocultural identity of the Kazakh diaspora of China at present. The authors, based on the analysis of scientific literature and materials of their own field research, have revealed that the structure of the ethnocultural identity of the Kazakhs of China, acquired as part of the diaspora, today acts as a combination of signs of ethnicity. In conclusion, the ethnocultural identity of the diaspora the prospects for its preservation and reproduction, are directly dependent on the political and socio-economic situation in the country of residence.